SISTEM PENGAMBILAN KEPUTUSAN DALAM PEMILIHAN ALAT KONTRASEPSI DENGAN METODE PROFILE MATCHING - RIZKY SANDY SYABANA (2020)
SDGs (Sustainable Development Goals) is a global action plan agreed by world leaders, including Jusuf Kalla as the vise president of Indonesia, to end poverty, inequality and protect the environment. By carrying out the principle to leave no one behind, it opens opportunities for developing countries to have the same opportunities as developed countries in achieving prosperity. One of the SDGs indicators in point 3 regulates the right to health, and one of its outputs ends the disease spreading, and ends the AIDS epidemic. One effort that can be done to deal with these problems is by knowing the selection of appropriate contraceptive methods. However, many cases show that the acceptor is not suitable in using the available contraceptives. Giving rise to side effects on the acceptor. The purpose of this study is to create a decision support system in choosing contraception that is suitable for the acceptor. In conducting this research, the writer used the Profile Matching method. This method was chosen because it is in accordance with the theme raised by the author. The criteria that the authors determined consisted of age, disease history, weight (BMI), breast milk, history of delivery, duration of use, and income. The results to be achieved in this study are an application that can help midwives or medical staff in providing recommendations to acceptors in selecting appropriate contraceptives, knowledge about contraception, and providing information for puskesmas for contraception procurement